Chloroplast-localized GUN1 contributes to the acquisition of basal thermotolerance in Arabidopsis thaliana - Lasorella, Cecilia; Fortunato, Stefania; Dipierro, Nunzio; Jeran, Nicolaj; Tadini, Luca; Vita, Federico; Pesaresi, Paolo; de Pinto, Maria Concetta (Frontiers in Plant Science, 2022)
Heat stress (HS) severely affects different cellular compartments operating in metabolic processes and represents a critical threat to plant growth and yield. Chloroplasts are crucial for heat stress response (HSR), signaling to the nucleus the environmental challenge and adjusting metabolic and biosynthetic functions accordingly. GENOMES UNCOUPLED 1 (GUN1), a chloroplast-localized protein, has been recognized as one of the main players of chloroplast retrograde signaling. Here, we investigate HSR in Arabidopsis wild-type and gun1 plantlets subjected to 2 hours of HS at 45°C. In wild-type plants, Reactive Oxygen Species (ROS) accumulate promptly after HS, contributing to transiently oxidize the cellular environment and acting as signaling molecules. After 3 hours of physiological recovery at growth temperature (22°C), the induction of enzymatic and non-enzymatic antioxidants prevents oxidative damage. On the other hand, gun1 mutants fail to induce the oxidative burst immediately after HS and accumulate ROS and oxidative damage after 3 hours of recovery at 22°C, thus resulting in enhanced sensitivity to HS. These data suggest that GUN1 is required to oxidize the cellular environment, participating in the acquisition of basal thermotolerance through the redox-dependent plastid-to-nucleus communication.